CIRCULATING IMMUNE COMPLEX DURING RAMADAN - Latifynia, A.; Vojgani, M.; Abofazeli, T.; Jafarieh, H. (Journal of Ayub Medical College Abbottabad, 2007)
Background: Fasting during Ramadan represent one of the five pillars of the Islamic religion. So it is important to know the effect of this kind of fasting on people’s life especially on their health. The purpose of this study was to show the effect of fasting during Ramadan on circulating immune complex (CIC) level and immune system. Methods: The CIC levels were measured before and after Ramadan by polyethylenglycole method. The blood samples were examined using quantitation chemiluminesence and circulating immune techniques. The results were analyzed using t-test and calculated coefficient correlation between CIC before and after Ramadan. Results: There was no significant difference between the CIC level before and after Ramadan. Conclusion: According to the results, fasting during Ramadan does not have bad effect on immune system of healthy people. Keywords: CIC; Ramadan; Fasting; Immune complex